The effects of drought treatments on biosynthesis and structure of maize starches with different amylose content. (1st December 2022) - Wu, Wenhao; Qu, Jianzhou; Blennow, Andreas; Herburger, Klaus; Hebelstrup, Kim Henrik; Guo, Ke; Xue, Jiquan; Xu, Renyuan; Zhu, Chuanhao; Zhong, Yuyue; Guo, Dongwei
Abstract: We investigated the effects of drought stress (DS) on maize varieties with different amylose content (AC). In starches with AC of 33 %, DS increased the contents of amylopectin (AP) chains with a degree of polymerization (DP) > 36 and decreased the AP chains with DP ≤ 36, while the AC was unchanged. DS decreased the crystallinity, the thickness of both amorphous and crystalline lamellae, and average granular size. In contrast, the digestibility increased. For starches with AC of 45 %, DS increased the content of AP chains with DP > 24 and AC, while the contents of AP chains with DP ≤ 24 decreased. DS produced starch with thinner crystalline lamellae, thicker amorphous lamellae, more elongated and larger granules. The digestibility of the starches decreased. In starches with AC of 53 %, moderate DS led to similar structural and functional changes as found for starches with AC of 45 %. Finally, severe DS resulted in the decrease of AC. Graphical abstract: Unlabelled Image